The Influence of Education Training and Teaching Experience on Teacher Professionalism in State High Schools in Seram Barat District, Seram Barat District - Arnold Sahalessy; Rileks Titabano; Vando Kristi Makaruku (International Journal of Education, Information Technology, and Others, 2022)
This study aims to analyze the effect of training education and teaching experience on the professionalism of public high school teachers in West Seram District, West Seram Regency. This research is a quantitative research with a correlational design. The population in this study were all vocational school teachers in Kairatu District and 83 teachers were selected as samples using the total sampling technique. The technique used to obtain through a closed questionnaire. Regression test statistics show that, (1) Training Education has a significant effect on teacher professionalism by 0.844 or 71.30%. The magnitude of this influence can be explained through the regression equation y ̂= 84.998+0.266x_1; (2) Teaching experience has a significant effect on professionalism by 0.940 or 88.30%. This influence can be explained through the regression equation, namely y ̂=17.176+0.824.; and (3) Education, training and teaching experience together. This effect can be explained through the regression equation y ̂ = 15.037+ 0.152x_1+ 0.738x_2.